O-267 Uterine volume is dramatically decreased in Stem Cell Hematopoietic Transplantation childhood survivors whatever the conditioning regimen. A case-control MRI study in the L.E.A cohort. (30th June 2022) - Courbière, B; Drikes, B; Gros, A; Hamidou, Z; Bertrand, Y; Gandemer, V; Poiree, M; Plantaz, D; Plat, G; Contet, A; Ansoborlo, S; Paillard, C; et al.
Abstract: Study question: What is the impact of the type of myeloablative conditioning (MAC) regimen applied for hematopoietic stem cell transplantation (HSCT) on uterine volume of childhood leukemia survivors? Summary answer: Uterine volume is significantly decreased after HSCT. Not only Total Body Irradiation (TBI), but also high-dose chemotherapy-based regimens containing alkylating agents induce uterine damage. What is known already: Premature ovarian failure after HSCT is well known, as well as the uterine damage induced by TBI on uterine volume. A few studies have reported smaller uterus after HSCT in women treated with chemotherapy only. In these studies, uterus volume was assessed by a transabdominal and/or transvaginal ultrasonography, and primary diagnosis, age at treatment and chemotherapy regimen were heterogeneous. These preliminary results suggested that alkylating agents could induce uterine damage, as well as they induce fibrosis and vascular damage in ovarian stroma. The impact of chemotherapy on myometrium and uterus is still few investigated. Study design, size, duration: A prospective multicentric national study was conducted between 2017, November and 2021, June in 16 University Teaching Hospitals that are following more than 4 500 childhood acute leukemia survivors enrolled in the L.E.A cohort. We included 88 adult women treated for a childhood acute leukemia with HSCT and who agreed a pelvic MRI assessment. Every case was matched 1:1 to control women who underwent MRI for benign ovarian cysts or benign pelvic pathology. Participants/materials, setting, methods: Pelvic MRI scans were performed with a 1.5-T or 3T magnetic resonance scanner, including diffusion-weighted imaging sequences. Scans were centralized for a double-blinded lecture by two radiologists. The main outcome was the uterine volume. The secondary outcomes were uterine body-to-cervix ratio and apparent diffusion coefficient (ADC). Univariate and multivariate analyses have investigated the association of clinical and imaging variables with conditioning regimen and age at HSCT. Main results and the role of chance: The mean age in HSCT group was 26.5 + 6.3 years. Mean age at HSCT was 9.1 + 0.3 years with a mean follow-up of 16.4 + 0.5 years. Among the 88 women included in HSCT group, two groups of conditioning regimens have been compared to the control group: a chemotherapy-only MAC regimen group with high dose of alkylating agents (n = 34) and one TBI-based regimen group (n = 52). Two MRI scans were not available. Among HSCT group, 75 women were considered as "normally impregnated" by estrogens, by hormone replacement therapy (HRT) for premature ovarian insufficiency (POI) or thanks to a residual ovarian function. Uterine volume was significantly decreased both after chemotherapy-only MAC regimen and after TBI, with respectively 45.3 + 5.6 and 19.6 + 1.9 mL Vs 79.7 + 3.3 mL in control population (p < 0.01). In chemotherapy-only MAC regimen group, uterine volume was dramatically decreased in POI women without HRT compared to those having a hormonal impregnation (15.2 + 2.6 Vs 49.3 + 6 mL, p < 0.05). In contrast, after TBI, uterine volume was similar in all women, with no positive effect of HRT on uterine volume (respectively 16.3 + 2.6 Vs 20.1 + 2.2 mL). Limitations, reasons for caution: The number of pregnancies obtained spontaneously or after oocyte donation in our study population was too low to evaluate the obstetrical impact of uterine damage caused by non-TBI regimens. Wider implications of the findings: Our results provide strong evidence that a MAC regimen containing high dose of alkylating agents could induce uterine damage. In these sub-group of women, HRT increases the volume of the uterus compared to non-treated women. After TBI, uterine volume is dramatically decreased, with no benefit of HRT on it. Trial registration number: NCT 03583294